Implementation of Management Systems in Increasing the Quality of Education at SMP IT Ibnu Kaldun Marelan - Amiruddin Amiruddin; Ahmad Ardhi Mauluddin Sitorus; Lydia Amelia; Rahmiatul Zuhro; Zahara Ahmad Fauzi (Universitas Muhammadiyah Enrekang, 2022)
This research is to determine the planning, implementation, evaluation, and implementation of management information systems in improving the quality of the educational process. This research uses a qualitative approach, namely the research method used to examine the condition of natural objects where the researcher is the key instrument. This article aims to explain the topic of management information systems in improving the quality of education in an educational institution. This research was conducted using a qualitative-descriptive method. The results of the research show that the information system for education quality management is (a) the quality improvement planning process for the management information system. (b) Implementation of quality improvement in the use of management information systems at the school, implemented in the curriculum through: 1) self-development programs. 2) integration into all subjects, and 3) habituation. (c) Evaluation of quality improvement in the learning process by utilizing management information systems. In improving the quality of education, teachers as educators have a very important position and strategy in developing the potential of students. To increase the professionalism of educators in learning, it is increased through ways of attending upgrading, attending educational courses, conducting visits to other schools or comparative studies, increasing reading, establishing relationships with student guardians, increasing the use of methods, improving materials, and improving facilities and infrastructure. Teachers as educators have a very important position and strategy in developing the potential of students. To increase the professionalism of educators in learning, it is increased through ways of attending upgrading, attending educational courses, conducting visits to other schools or comparative studies, increasing reading, establishing relationships with student guardians, increasing the use of methods, improving materials, and improving facilities and infrastructure.